The Effects of Special Autonomy Fund and Oil and Gas Revenue Sharing on education spending and the Quality of Education: The case of Districts and Cities in Aceh - Muhammad Isa, Islahuddin, Nadirsyah. (Universitas Syiah Kuala, 2015)
Abstract : As a special autonomy region in Indonesia, Aceh is entitled to additional fund of special autonomy and oil and gas revenue sharing. Education sector has become a main focus to utilize these funds. Therefore, the issue of special autonomy related funds and its association with the quality of education is interesting to study. Data were collected based on documents and reports available in Directorate General of Fiscal Balance of The Indonesian Ministry of Finance and Aceh Development Board. The results showed that special autonomy fund and oil and gas revenue sharing provide a positive effect on the allocation of education spending.Further analysis showed that the allocation of education spending provide a positive effect on the quality of education.Keywords: Quality of education, allocation of education spending, Special Autonomy Fund, oil ang gas shared revenuen